Iraq : First Review Under the Stand-By Arrangement, Request for Waiver of Nonobservance of a Performance Criterion, Waiver of Applicability, and Rephasing of Access. (IMF Staff Country Reports; Country Report ;, 2010)
The authorities view the program as providing a valuable anchor for their macroeconomic policies during a period of high economic and political uncertainty, and providing access to budget financing. The discussions for this review were delayed owing to lengthening data lags resulting from the attacks on the Ministry of Finance and the Central Bank of Iraq (CBI). With the projected increase in oil production and exports in the coming years, Iraq will be able to strengthen its fiscal and external positions and speed up the rebuilding of its institutions and infrastructure.